PA 07-1-0534 An exploration of the factors associated with unintentional paediatric burn injuries in rural and peri-urban malawi: a qualitative study. (November 2018) - Beard, Maria; Watson, Michael C; Clifford, Michael
Abstract : Background: Malawian children are at high risk of burn injuries due to the nature of their environments and paucity of burn prevention programmes. Moreover, data which reports the burden of burn injuries has often been limited to the interpretation of hospital-based records which only provides the pattern of burns which attend medical facilities, but does not reflect the household context or perceptions of such injuries necessary to create culturally appropriate prevention initiatives. Objective: To explore the factors associated with paediatric burn injuries in rural and peri-urban Malawi Methods: A qualitative approach explored cultural and contextual factors associated with paediatric burn injuries across four sites in Malawi. Data was collected through household observations, interviews and focus groups. Interviews were also conducted with a sample of health professionals and key informants. Findings: Parents are limited in their ability to provide adequate protection from burn injuries due to a lack of: knowledge about injury prevention, safety equipment, control to make alterations to their housing and ability to adequately supervise children. Health professionals reported they were unable to consistently provide information to parents and caregivers about burns prevention due to a lack of time and resources. Conclusion: The factors associated with paediatric burn injuries in Malawi are multifaceted and intertwined by the complex nature of the household environment and those who live within it. Importantly, this study provides a starting point from which to understand these factors and gives a voice to those affected. Policy implications: There is an urgent need to raise an awareness of the burns problem to policy makers, health professionals, parents as well as government and non-government organisations to initiate the development of comprehensive prevention initiatives. Future strategies need to consider the integration of multilevel support to address the challenges faced by families living in rural and peri-urban Malawi.